In vivo characterization of the physicochemical properties of polymer-linked TLR agonists that enhance vaccine immunogenicity - Lynn, Geoffrey M; Laga, Richard; Darrah, Patricia A; Ishizuka, Andrew S; Balaci, Alexandra J; Dulcey, Andrés E; Pechar, Michal; Pola, Robert; Gerner, Michael Y; Yamamoto, Ayako; Buechler, Connor R; Quinn, Kylie M; et al. (Nature biotechnology, 2015)
The efficacy of vaccine adjuvants such as Toll-like receptor agonists (TLRa) can be improved through formulation and delivery approaches. Here, we attached small molecule TLR-7/8a to polymer scaffolds (polymer-TLR-7/8a) and evaluated how different physicochemical properties of the TLR-7/8a and polymer carrier influenced the location, magnitude and duration of innate immune activation in vivo. Particle formation by polymer-TLR-7/8a was the most important factor for restricting adjuvant distribution and prolonging activity in draining lymph nodes. The improved pharmacokinetic profile by particulate polymer-TLR-7/8a was also associated with reduced morbidity and enhanced vaccine immunogenicity for inducing antibodies and T cell immunity. We extended these findings to the development of a modular approach in which protein antigens are site-specifically linked to temperature-responsive polymer-TLR-7/8a adjuvants that self-assemble into immunogenic particles at physiologic temperatures in vivo. Our findings provide a chemical and structural basis for optimizing adjuvant design to elicit broad-based antibody and T cell responses with protein antigens.
Keywords: vakcíny; Adjuvants, Immunologic; Toll-Like Receptors; T-Lymphocytes; Drug Carriers; adjuvancia imunologická; Female; zvířata; myši; myši inbrední C57BL; Mice; toll-like receptory; ženské pohlaví; Male; Vaccines; Mice, Inbred C57BL; nosiče léků; T-lymfocyty; Animals; mužské pohlaví